2005
DOI: 10.1007/s10072-005-0498-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis and lifestyle factors: the Hordaland Health Study

Abstract: This study compared multiple sclerosis (MS) patients (n=87) with the general population and with people reporting angina pectoris (n=109), asthma (n=1353) and diabetes (n=219) regarding health-related quality of life (SF-12), working status and lifestyle factors including smoking, alcohol consumption, body mass index (BMI) and leisure physical activity. The study was cross-sectional and included the birth cohorts from 1950 to 1957 living in Hordaland County, Norway in 1997. A total of 22 312 people participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 24 publications
4
45
1
1
Order By: Relevance
“…Findings from case-control studies concerning the association between lifestyle factors and risk of MS have been conflicting. Our results are in accordance with those recently published from case-control studies [5,8] and cohort studies which were carried out in USA and Norway [7,9] . On the contrary, in the case-control study done in Ferrara (Italy) [6] , no significant difference was observed between MS cases and controls.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Findings from case-control studies concerning the association between lifestyle factors and risk of MS have been conflicting. Our results are in accordance with those recently published from case-control studies [5,8] and cohort studies which were carried out in USA and Norway [7,9] . On the contrary, in the case-control study done in Ferrara (Italy) [6] , no significant difference was observed between MS cases and controls.…”
Section: Discussionsupporting
confidence: 83%
“…The findings from a few studies in which the relationship between drinking habits and development of MS was analyzed are rather inconsistent [9,25,26] . It has been suggested that questionnaire-based assessment of alcohol consumption in these studies is difficult because of variable measurement of alcohol intake and possible recall bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 A recent study among 118 patients with MS found that, after diagnosis, 38% of participants stopped physical activity and many reduced frequency of activity. 31 In our study, participants could have possibly reduced physical activity in response to prediagnosis symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the absence of data on smoking and BMI may have led to an overestimation of the association between MS and fracture risk. 37,38 Information on the degree of disability in patients with MS was lacking too, as well as information on the course of each patient's disease and data on medication that has been administered in hospitals. Because patients with MS in our study were included based on a hospital registration, there may have been a selection bias toward patients with more severe MS.…”
Section: Discussionmentioning
confidence: 99%